Design of low-power high speed error-tolerant adder and its application in digital signal processing - Zhang, Weijia (2009)
As technology advances, errors/defects in integrated circuits become unavoidable. At the same time, the pursuit of low-power and high-speed circuits is always restricted by the conventional circuit design technology. In this context, several new technologies that regard the accuracy of circuit as a new design parameter other than the conventional design metrics have been proposed. These technologies trade the accuracy of circuit for the improvements in power consumption and/or speed performance.